Advocating for Sustainable Work: A Legal Perspective on Labor Regulation and Human Resources Practices in Indonesian Higher Education - Mursidah, Siti; Wulandari, Cahya; Khoiruddin, Moh.; Hassan, Muhamad Sayuti; Fauzi, Ricky Dermawan; Nugroho, Andre Setyo (Indonesian Journal of Advocacy and Legal Services, 2025)
This study examines the implementation of labor regulations aligned with the Sustainable Development Goals (SDGs) within the context of human resource (HR) management at Universitas Negeri Semarang (UNNES), a leading institution in Indonesia’s higher education sector. As universities are expected to model sustainable and equitable employment practices, this research explores how labor laws—particularly those concerning decent work, gender equality, and inclusive employment—are applied in institutional HR policies and practices. Employing a normative juridical approach supported by empirical data, the study analyzes the legal frameworks governing labor rights in Indonesia and their integration into HR procedures at UNNES. The findings reveal a partial but growing compliance with SDGs-based labor principles, highlighting areas where legal advocacy and institutional commitment are still needed to ensure fair labor standards. The study further discusses the role of legal services and advocacy in advancing labor justice and institutional accountability within higher education settings. By focusing on the intersection of labor law, sustainability, and human resource management, this paper contributes to the broader discourse on legal reform and advocacy for sustainable work environments in Indonesian universities.